IN-SILICO ANALYSIS OF METHOXYL PECTIN COMPOUNDS FROM BANANA PEELS AS HMG-COA REDUCTASE INHIBITOR COMPLEXES - Tapiory, Adelia Adrianne; Pertiwi, Kadita Octavia; Fadilla, Khalisa; Reyhanditya, Davy; Fatchiyah, Fatchiyah (JSMARTech, 2020)
Cardiovascular disease (CVD) is one of the most important health problems that emerge in the last decade. The major factor of the disease is by the high level of cholesterol in blood. Several ways can be used to reduce the amount of cholesterol in blood, as using HMGR treatment. This enzyme acts as catalyst in the initial step and limits the cholesterol biosynthesis. Pectin is a polysaccharide compound that used as an agent to reduce the total cholesterol in bloods. In this research, we aim to analyze the function of methoxyl pectin in inhibiting excessive cholesterols in blood by binding with the HMGR. The method we used in this research, first step searching data mining from database and preparation of protein and ligands using discovery studio. Molecular docking analyzed via HEX software. The result of molecular docking is visualized using discovery studio to analyze the energy binding level, also the bonds that formed and the impact that comes from the bonds. The results show that HMGR binding energy for native ligand (HMGCoA) as control ligand was -450,2 kJ/mol, methoxyl pectin was -177,3 kJ/mol and atorvastatin, a group of drugs commonly used for CVD treatment was -386,6 kJ/mol. HMGR binds to HMGCoA with 7 hydrogen bonds and a hydrophobic bond. Methoxyl pectin binds to HMGR with residue Glu700 and His625. Atorvastatin binds to HMGR with residue Lys633 and Leu634. It is known that native ligands bind to HMGR when cholesterol goes down. Based on research, methoxyl pectin bond with HMGR is the same as the HMGCoA native ligand with HMGR, namely His635. This shows that methoxyl pectin is predicted to inhibit HMGR and resulting LDL cholesterol decrease. Methoxyl pectin is indicated to be an alternative drug for cardiovascular disease considering that atorvastatin has several side effects. While methoxyl pectin, which is derived from natural ingredients with minimum side effect.